The utility of the neutrophil-to-lymphocyte ratio in predicting urolithiasis in acute abdominal pain accompanied by flank pain - Akgün, Feride Sinem; Sinanoğlu, Orhun (The European Research Journal, 2019)
Objectives: To evaluate whether the neutrophil-to-lymphocyte ratio (NLR), can differentiate between urinary stone disease and inflammatory conditions in patients admitted to emergency department having acute abdominal pain accompanied by flank pain.Methods: Data of 191 patients with acute abdominal pain accompanied by flank pain admitted to emergency department in a single institution during 1 year period was retrospectively reviewed. Complete blood count and urine analysis were evaluated, the definitive diagnosis was established radiologically. The NLR was calculated as the absolute neutrophil count divided by the absolute lymphocyte count. The cut off value for the NLR in relation to stone status was calculated.Results: Of the 191 patients 51.3% (n = 98) were males, 48.7% (n = 93) were females (p > 0.05). White blood counts of the patients according to the presence of stone does not show a statistically significant difference (p > 0.05). NLR measurement of patients according to the presence of stone shows a statistically significant difference (p = 0.009). NLR of patients with urinary stones were significantly lower than patients without urinary stones. NLR measurements did not differ significantly according to stone location. A cut-off point of ≤ 2.16 for the NLR was determined according to the stone status of the patients. NLR values were higher in patients with acute abdominal pain/flank pain due to inflammatory pathologies. Conclusion: As the diagnosis and treatment of urolithiasis take long time and require elaborate methods, NLR may be used as a simple method in the differential diagnosis of pain due to urinary stone disease or inflammatory condition.